Optimization of Promotional Marketing Strategies on Consumer Buying Interest in Okoy Flower Garden Restaurant - Kalangi, Jola Silvana; Tulungen, Franky R.; Pangkey, Deisy A.P.J.; Lintong, Elsje; Gumerung, Jeffry; Kalalo, Rieneke R. (Interdisciplinary Social Studies, 2022)
The era of business competition in culinary field has experienced drastic changes along with the emergence of the Covid-19 Pandemic and the era of digitalization which requires every business actor to move on to the internet communication and information network. This development will certainly make the restaurant of Okoy Flower Garden Tomohon survive and continue to exist to serve consumers. The purpose of this study is to optimize the restaurant's marketing strategy in order to increase consumer buying interest. The research approach was more directed at quantitative methods with causal research on each of the variables studied. This study showed that the promotional strategy carried out by Okoy Flower Garden has not been implemented optimally. The effect of promotion has not been able to significantly increase consumer buying interest. The marketing strategy in terms of promotion in order to attract consumer buying interest has not been implemented optimally. The marketing strategy for promotion that does not have a strong effect on consumer buying interest at Okoy Flower Garden can be seen from the regression coefficient of the Consumer Buying Interest value of 0.135. The regression coefficient is positive, so it can be stated that the direction of the influence of the variable X on Y is positive.